COPY NUMBER VARIATION DETERMINATION, METHODS AND SYSTEMS (2013)
The present invention methods and systems for determining copy number variation of a target polynucleotide in a genome of a subject including amplification based techniques. Methods can include pre-amplification of the sample followed by distribution of sample and a plurality of reaction volumes, quantitative detection of a target polynucleotide and a reference polynucleotide, and analysis so as to determine the relative copy number of the target polynucleotide sequence in the genome of the subject.